Mechanical and structural comparison between primary tumor and lymph node metastasis cells in colorectal cancer1. Issue 28 (28th July 2015) - Palmieri, V.; Lucchetti, D.; Maiorana, A.; Papi, M.; Maulucci, G.; Calapà, F.; Ciasca, G.; Giordano, R.; Sgambato, A.; De Spirito, M.
<x xml:space="preserve">Abstract</x> Regulation of cell mechanics allows cancer cells to acquire specialized functions. Primary tumor soft rounded cells are responsible for tumor volume increase, while elongated stiff cells invade neighbouring tissues. Once reached the lymph node, cells reorganize actin and increase adhesion to cope with high shear forces.